Successful treatment of pityriasis lichenoides chronica with narrow-band ultraviolet B therapy in a patient with keratitis-ichthyosis-deafness syndrome: A case report - (:unkn) unknown (Dermatology Online Journal, 2016)
Keratitis-ichthyosis-deafness (KID) syndrome is a rare genodermatosis causing ichthyosis-like skin lesions, keratitis, and deafness. Herein, we report a patient with this rare syndrome in association with pityriasis lichenoides chronica, which was succesfully treated with narrow-band ultraviolet B phototherapy despite our concerns regarding the increased risk of squamouscell carcinoma, hyperpyrexia, and keratitis. © 2016 by the article author(s).